2021
DOI: 10.3390/ijms22115700
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Expression of SMPD1 Encoding Acid Sphingomyelinase Decreases upon Antidepressant Treatment

Abstract: Major depressive disorder (MDD) is a severe psychiatric condition with key symptoms of low mood and lack of motivation, joy, and pleasure. Recently, the acid sphingomyelinase (ASM)/ceramide system has been implicated in the pathogenesis of MDD. ASM is a lysosomal glycoprotein that catalyzes the hydrolysis of sphingomyelin, an abundant component of membranes, into the bioactive sphingolipid ceramide, which impacts signaling pathways. ASM activity is inhibited by several common antidepressant drugs. Human and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…A low dose of radiation (2 Gy) upregulates miR-15a and lowers SMPD1 levels, whereas a high dose of radiation (more than 10 Gy) lowers miR-15a and activates the SMPD1 gene, increasing ASM biosynthesis. Antidepressant treatment also decreases expression of SMPD1-mRNA [128]. In a similar manner, the NO-donor diethylenetriamine/NO also decreased mRNA and protein expression of ASM in HepG2 cells, triggering apoptosis and cell death [129].…”
Section: Can Secreted Asm Act At Cellular Membrane Surfaces Directly?mentioning
confidence: 70%
“…A low dose of radiation (2 Gy) upregulates miR-15a and lowers SMPD1 levels, whereas a high dose of radiation (more than 10 Gy) lowers miR-15a and activates the SMPD1 gene, increasing ASM biosynthesis. Antidepressant treatment also decreases expression of SMPD1-mRNA [128]. In a similar manner, the NO-donor diethylenetriamine/NO also decreased mRNA and protein expression of ASM in HepG2 cells, triggering apoptosis and cell death [129].…”
Section: Can Secreted Asm Act At Cellular Membrane Surfaces Directly?mentioning
confidence: 70%
“…One study reported that hippocampal atrophy in female MDD patients was mainly limited to the posterior cluster [27]. Moreover, the effect of amitriptyline was observed specifically in the dorsal hippocampus [28]. Based on these observations, we infer that the volumetric reductions in the L1, L2, L3, and R4 subfields of the hippocampus can serve as imaging markers of mood disorders and cognitive impairment in MDD.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, ASMase and ceramide levels are also highly elevated, resulting in mitochondrial dysfunction and apoptosis [ 43 , 44 , 45 ]. However, the functional inhibitors of acid sphingomyelinase detach ASMase from the lysosomal inner membrane and degrade it [ 46 ]. Therefore, we hypothesized that one of the ASMase inhibitors, imipramine, may reduce TBI-induced neuronal death and cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, under pathologic conditions, ASMase and ceramide levels are abnormally increased and induce neuronal death. In this study, we used imipramine, which attached to the lysosomal membrane instead of ASMase [ 31 , 46 ]. ASMase is most activated 2–3 h after injury [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%